IMPLEMENTASI E-GOVERNMENT PADA PEMERINTAH DAERAH - Karman Karman; Rudi Deswanto; Sri Adhi Ningsih (Jurnal Studi Ilmu Pemerintahan, 2021)
E-Government or Electronic-Based Government System is a concept carried out by government institutions in providing services to the community more effectively and efficiently. There are problems that continue to occur related to the development of the Electronic-Based Government System, namely the security sector. The security sector must be the focus in implementing public services. The amount of information that must be managed with a high level of sensitivity. Serious attention is needed on how safe conditions are in developing the implementation of an Electronic-Based Government System. This study uses the Systematic Literature Review method to be able to identify and analyze research trends related to the level of security in Electronic-Based Government Systems collected from 2015-2019. The results of this study indicate that there are many factors that require the government to prioritize more safety factors in implementing SPBE. In addition, there are various solutions in the form of models/frameworks in solving problems in applying the concept of security to an Electronic-Based Government System.